2003
DOI: 10.1063/1.1524618
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular structure of helical ribbons self-assembled from a β-sheet peptide

Abstract: We have investigated the supramolecular structure of helical ribbons formed during self-assembly of a ␤-sheet peptide using computer simulation. We tested a wide range of molecular packing geometries consistent with the experimental dimensions to identify the most stable structure, and then systematically changed the helical geometry to investigate its energy landscape. The effect of pH was incorporated by scaling the amount of charge on the side chains based on the electrostatic double layer theory. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 42 publications
(50 reference statements)
8
109
1
Order By: Relevance
“…Its dipole moment is significantly lower than the actual peptides (6.4 Debyes versus 52-100 Debyes measured from the center of geometry) and the simulation showed reduced preference for the antiparallel configuration; it was found to be 52.5%, compared to 60.2% for A␤ 7g . Although the preference for an antiparallel configuration is slight at the dimer level, the distinction in fibrils is likely to be cooperative in nature so that the bias could become stronger for more extended ␤-sheet structures (20,27). For example, in previous simulations of a ␤-sheet formed from 40 KFE8 monomers, it was found that an antiparallel ␤-sheet maintained its structure, whereas a parallel ␤-sheet did not (27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its dipole moment is significantly lower than the actual peptides (6.4 Debyes versus 52-100 Debyes measured from the center of geometry) and the simulation showed reduced preference for the antiparallel configuration; it was found to be 52.5%, compared to 60.2% for A␤ 7g . Although the preference for an antiparallel configuration is slight at the dimer level, the distinction in fibrils is likely to be cooperative in nature so that the bias could become stronger for more extended ␤-sheet structures (20,27). For example, in previous simulations of a ␤-sheet formed from 40 KFE8 monomers, it was found that an antiparallel ␤-sheet maintained its structure, whereas a parallel ␤-sheet did not (27).…”
Section: Resultsmentioning
confidence: 99%
“…Although the preference for an antiparallel configuration is slight at the dimer level, the distinction in fibrils is likely to be cooperative in nature so that the bias could become stronger for more extended ␤-sheet structures (20,27). For example, in previous simulations of a ␤-sheet formed from 40 KFE8 monomers, it was found that an antiparallel ␤-sheet maintained its structure, whereas a parallel ␤-sheet did not (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphipathic β-sheet peptides composed of alternating hydrophobic and hydrophilic amino acids (with general sequence (XZXZ)n where X is nonpolar and Z is polar) are a privileged class of self-assembling peptide that have been widely used in the design of hydrogel materials [4]. The (FKFE)2 peptide is a prominent member of this class of material that has been frequently studied [5,6]. This peptide self-assembles into putative β-sheet bilayer nanoribbons; molecular dynamics studies suggest that the alignment of peptides within the β-sheet structure requires the N-terminal Phe residue to "dangle" out of register ( Figure 1) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The (FKFE)2 peptide is a prominent member of this class of material that has been frequently studied [5,6]. This peptide self-assembles into putative β-sheet bilayer nanoribbons; molecular dynamics studies suggest that the alignment of peptides within the β-sheet structure requires the N-terminal Phe residue to "dangle" out of register ( Figure 1) [6]. We have adopted this peptide specifically to understand the impact of general hydrophobic and more specific aromatic π-π effects on peptide self-assembly [7,8].…”
Section: Introductionmentioning
confidence: 99%